In conversation W.V. Quine. (London Philosophy International, 1994)
Professor Quine is questioned by the guest panelist, George Boolos about his arguments in "Two Dogmas of Empiricism."
Keywords: Van Orman Quine, Willard; Van Orman Quine, Willard; Empiricism